THE EFFECT OF HYPOTHYROIDISM ON OFFSPRING IN AN EXPERIMENT ON LABORATORY ANIMALS - Azizova Feruza Khusanovna; Mirzamukhamedov Odiljon Xadjiakbarovich; Choriyev Beruniy; Sobirova Dildora Ravshanovna; Mahmudova Shakhlo Ismatullayevna; Umarova Zulfiya Khosilovna (Galaxy International Interdisciplinary Research Journal, 2023)
The morphological changes in the myocardium of the offspring were studied when the mother had hypothyroidism in the rat to the female mother during the feeding of the rats.